Development of Didactic Understanding - Arsić, Zvezdan M.; Banđur, Veljko R. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The notion of didactics was differently defined in the period of its intensive development, which required that its subject matter be defined differently, as well. For this reason, the paper focuses on the development of didactic understanding from the beginnings to contemporary notions of didactics as a scientific discipline in the system of pedagogical sciences. In addition, the authors’ views are presented and analysed in order to best explain these trends. The work is divided thematically into several periods and areas: the development of didactic thought and theory up to J. A. Comenius; the significance of J. A. Comenius and his work to the further development of didactics; the basic features of creativity in the field of didactic theory and practice after J. A. Comenius; and modern viewing of the concept and subject of didactics.